2004
DOI: 10.1086/421121
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Influenza in Older Adults with Chronic Obstructive Pulmonary Disease

Abstract: TVV+CAIV-T appeared more immunogenic than TVV+P, but the observed difference may be clinically unimportant. Anti-influenza serum and nasal-wash antibodies were associated with immune protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Titers ≥ 160 were also seen more often after ADV than TIV and are reportedly more predictive of protection than the standard threshold. [27][28][29] While statistically significant, the differences in seroprotection rates and GMT ratios after ADV or TIV were of modest magnitude. Baseline titers of the annually immunized study participants were moderately high, which might have reduced potential differences in responses to both vaccines.…”
Section: Discussionmentioning
confidence: 93%
“…Titers ≥ 160 were also seen more often after ADV than TIV and are reportedly more predictive of protection than the standard threshold. [27][28][29] While statistically significant, the differences in seroprotection rates and GMT ratios after ADV or TIV were of modest magnitude. Baseline titers of the annually immunized study participants were moderately high, which might have reduced potential differences in responses to both vaccines.…”
Section: Discussionmentioning
confidence: 93%
“…17 The correlation between HI titer and vaccine efficacy in adults 65 years and older is not well established, although higher titers are associated with lower risk of influenza infection from H3N2 and B strains. 11,21 HI is able to quantify the antibody response to the globular head of influenza hemagglutinin, but HI cannot assess the quality of the antibodies to neutralize infection. In older adults who have likely had natural exposure to numerous influenza strains of the same subtype, protective humoral responses are best directed at the initial infecting strain due to "original antigenic sin," and would likely vary by age due to potential infection by H1N1 viruses before 1957.…”
Section: Discussionmentioning
confidence: 99%
“….0001 showing them to be a strong CoR, whereas the titers of antibody to PR8 strain A are weakly associated ( ) and, hence, P p .08 are a poor CoR. Subsequent studies of influenza virus infection demonstrated an association between strain-specific antibody titers and infection or morbidity, substantiating this immunological measurement as a CoR [24].…”
Section: Correlate Of Risk (Cor)mentioning
confidence: 90%